Theoretical Analysis on the Stability of Single Bulk Nanobubble - Wang, Yao; Zhou, Limin; Hu, Jun; Zhang, Lijuan (Frontiers in Materials, 2022)
As predicted by classical macroscopic theory, the lifetime for nanoscale gas bubbles is extremely short，, which is conflicting with the detecting of stable bulk nanobubbles from the experimental aspectly in recent years. In fact, the stability of a bulk nanobubbles depends on surrounded liquid environment. Also, the dynamic process of gas in water involves in the dissolution, diffusion, releasing and transportation gas as well as the property of nanobubbles inside. Moreover, the X-ray absorption spectrum data analysis of scanning transmission X-ray microscopy (STXM) revealed that the gas density inside was 2 orders of magnitude higher than that in atmospheric pressure, and bubbles were found in a super-saturated liquid environment (JACS 2020, 142, 5583-5593). In this studyHere, based on previous reports, we introduce the gas transport parameter l in the classical diffusion equation by considering the gas diffusion near the bulk nanobubble at different locations in a container, and consider the MacLeod-Sugden relationship between the surface tension and densities of liquid and gas for computing the lifetime of single bulk nanobubble in an open system. The results show that the single nanobubble lifetime depends on the inner density and gas transport length. It could reach to the order of 10 s-102 100 s for the single nanobubble with an initial radius of 200 nm, and provides a new idea to prolong the lifetime of the single bulk nanobubble. Meanwhile, compared with the continuous influence of the inner density on the gas diffusion flux near the nanobubble, the range of the gas transport near the nanobubble on the gas diffusion flux is limited, which is affected by the dissolution time of the nanobubble. Our findings would be helpful to explore the storage conditions of nanobubbles and the mechanism of mass transfer at the gas-liquid interface at the micro scale.